2008
DOI: 10.1007/s11606-008-0629-6
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Sustained Walking among Diabetes Patients in Managed Care: The Translating Research into Action for Diabetes (TRIAD) Study

Abstract: Pain, obesity, and new comorbidities were moderately associated with decreases in sustained walking. Whereas controlled intervention studies are needed, prevention, or treatment of these adverse conditions may help patients with diabetes sustain walking behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Daily walking for at least 20 min was less frequent in patients older than 65 years of age than in younger patients (64 vs. 70%); in women less frequent than in men (65 vs. 70%); and in whites or African Americans less frequent than in Asian/Pacific Islanders or Latino patients (49). Less education was also associated with a lower likelihood of regular physical activity (48).…”
Section: Patient Factorsmentioning
confidence: 97%
See 1 more Smart Citation
“…Daily walking for at least 20 min was less frequent in patients older than 65 years of age than in younger patients (64 vs. 70%); in women less frequent than in men (65 vs. 70%); and in whites or African Americans less frequent than in Asian/Pacific Islanders or Latino patients (49). Less education was also associated with a lower likelihood of regular physical activity (48).…”
Section: Patient Factorsmentioning
confidence: 97%
“…Obesity was more frequent in women than men (61 vs. 51%) and in African American participants and was associated with lower likelihood of regular walking (49). Obesity was also associated with a lower likelihood of being in control for all three cardio-metabolic risk factors but explained little of the poorer risk factor control in African Americans (26).…”
Section: Patient Factorsmentioning
confidence: 99%
“… found that US veterans reporting pain were less likely to follow a recommended eating and exercise plan than those without pain. In the Translating Research into Action for Diabetes study, reports of new or ongoing pain at baseline were associated with decreases in sustained walking at follow‐up ; thus, pain may be a barrier to self‐management behaviours, which may in turn worsen glycaemic control.…”
Section: Introductionmentioning
confidence: 99%